Oncologic PET/CT interpretation and reporting approaches - Karantanis, D.; Kalkanis, D.; Allen-Auerbach, M. S.; Herrmann, K.; Pomykala, K. L.; Bogsrud, T. V.; Lowe, V. J.; Czernin, J. (Nuklearmedizin - NuclearMedicine, 2014)
Aim: To elucidate techniques most commonly used for interpreting oncologic PET/CT studies. This survey forms a basis to work on standardization of reporting and highlight the most important issues to be addressed. Methods: A web-based survey of 329 PET/CT imaging specialists was designed with the intent to determine image interpretation patterns. The questionnaire consisted of 19 questions. Of the 329 participants, 230 were nuclear medicine specialists, 46 were radiologists, and 53 had dual-board certification. Results: Report of standardized uptake values (SUV) is not consistent; only 50.2% of respondents always report SUVs, while 45.2% report only if needed or requested. 80.9% of respondents indicated that reporting of SUV is only appropriate when its limitations are understood whereby a large majority prefer to report SUVmax. Maximum intensity projection (MIP) images are almost always reviewed by 91.1% of the respondents. An accurate and detailed clinical history is considered an essential element for reading PET/ CT studies by 84.0%, but only 20.7% report that this is always available. The most common self-reported average time for reviewing and reporting of whole body PET/CT (with no prior comparison scan) was 15-20 min (27.5%). Conclusion: PET readers have considerable reservations regarding the use and reporting of SUVs. SUVmax is more frequently used than SUVmean. Evaluation of MIP images is considered an important element of PET/CT interpretation. Although availability of sufficient patient’s history is considered essential, this is rarely available.
Keywords: Survey; FDG; standard uptake value; SUV; maximum intensity projection; limitations